2013
DOI: 10.1371/journal.pbio.1001485
|View full text |Cite
|
Sign up to set email alerts
|

Partial Inhibition of Adipose Tissue Lipolysis Improves Glucose Metabolism and Insulin Sensitivity Without Alteration of Fat Mass

Abstract: Partial inhibition of adipose tissue lipolysis does not increase fat mass but improves glucose metabolism and insulin sensitivity through modulation of fatty acid turnover and induction of fat cell de novo lipogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
147
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(158 citation statements)
references
References 50 publications
4
147
2
1
Order By: Relevance
“…Therefore, we assessed whether IR in WAT leads to decreased lipid synthesis and storage in HFD-fed AKO/cTg mice. GTT, ITT, and hyperinsulinemic/euglycemic clamp experiments, however, clearly showed that AKO/cTg mice were much more glucose tolerant and insulin sensitive than insulinresistant HFD-fed WT/cTg mice or mice lacking HSL (42) or MGL (43). Abolished HGP, increased muscle glucose uptake, and a pronounced antilipolytic WAT response to insulin confirmed that all classical insulin target tissues remained insulin sensitive in HFD-fed AKO/cTg mice and disproved the concept that IR prevented efficient lipid storage in this model.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, we assessed whether IR in WAT leads to decreased lipid synthesis and storage in HFD-fed AKO/cTg mice. GTT, ITT, and hyperinsulinemic/euglycemic clamp experiments, however, clearly showed that AKO/cTg mice were much more glucose tolerant and insulin sensitive than insulinresistant HFD-fed WT/cTg mice or mice lacking HSL (42) or MGL (43). Abolished HGP, increased muscle glucose uptake, and a pronounced antilipolytic WAT response to insulin confirmed that all classical insulin target tissues remained insulin sensitive in HFD-fed AKO/cTg mice and disproved the concept that IR prevented efficient lipid storage in this model.…”
Section: Discussionmentioning
confidence: 94%
“…One potential mechanism contributing to improved insulin sensitivity and glucose metabolism in Ad-GsKO mice is reduced lipolysis in adipose tissue resulting in lower circulating FFA levels. It is well established that FFAs, the major product of lipolysis, cause deleterious effects on insulin sensitive organs (32,33) and that genetic or pharmacologic inhibition of adipose tissue lipolysis in mice improves glucose metabolism and insulin sensitivity (29,34). Moreover, high lipolysis rate is associated with low insulin sensitivity in humans (34).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that FFAs, the major product of lipolysis, cause deleterious effects on insulin sensitive organs (32,33) and that genetic or pharmacologic inhibition of adipose tissue lipolysis in mice improves glucose metabolism and insulin sensitivity (29,34). Moreover, high lipolysis rate is associated with low insulin sensitivity in humans (34). The lower TG content in liver present in Ad-GsKO may also contribute to improved glucose metabolism in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…After a 2.5-h adaptation period, blood sampling was initiated at 13:00. Samples were drawn at 13:00, 14 7,15,30,45,60,90, and 120 min after glucose load. Samples (30-150 µl, with total loss <5% of blood volume) were collected in potassium-EDTA tubes and centrifuged.…”
Section: Surgical Preparationmentioning
confidence: 99%